Recognizing Stuve–Wiedemann syndrome in childhood: clinical insights from 11 patients with founder and novel LIFR variants - Gizem Ürel Demir; Nazlı Büşra Açıkgöz; Gülen Eda Utine; Pelin Özlem Şimşek Kiper (The Turkish Journal of Pediatrics, 2026)
Background. Stuve–Wiedemann syndrome is a rare autosomal recessive bent-bone dysplasia characterized by dysautonomia and distinctive skeletal abnormalities, most commonly caused by biallelic LIFR variants. Methods. Eleven patients from ten unrelated families with molecularly confirmed Stuve–Wiedemann syndrome were evaluated. Detailed demographic, perinatal, clinical, radiographic, and molecular data were collected. All patients underwent Sanger sequencing of LIFR. Results. Respiratory problems and episodic hyperthermia were present in all patients, while feeding difficulties, hypotonia, growth failure, developmental delay, craniofacial dysmorphism, oral abnormalities, and ocular involvement were also common. All patients demonstrated long-bone bowing, cortical thickening, and flared metaphyses. A biallelic LIFR variant was identified in all patients, occurring in the homozygous state in nine patients and in the compound heterozygous state in two patients. The recurrent c.2074C>T; p.(Arg692Ter) variant was homozygous in seven patients and compound heterozygous in one patient. Three novel LIFR variants were also identified. Conclusion. Stuve–Wiedemann syndrome is characterized by a high mortality rate during the first two years of life due to severe dysautonomia, and orthopedic complications worsen progressively with age; therefore, early diagnosis and lifelong multidisciplinary follow-up are essential. Furthermore, the high rate of consanguinity in Türkiye, together with the recurrent p.(Arg692Ter) variant in LIFR identified in multiple unrelated families, supports the possibility of a founder effect and suggests that the frequency of Stuve–Wiedemann syndrome in our population may be higher than expected. Our findings further characterize the previously reported clinical manifestations of Stuve–Wiedemann syndrome while expanding the molecular spectrum through the identification of three novel LIFR variants.